2016
DOI: 10.4103/0366-6999.186645
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Study of the Fixation Strength of Anteromedial Plating for Humeral Shaft Fractures

Abstract: Background:Open reduction and internal fixation with plate and screws are the gold standard for the surgical treatment of humeral shaft fractures, this study was to compare the mechanical properties of anteromedial, anterolateral, and posterior plating for humeral shaft fractures.Methods:A distal third humeral shaft fracture model was constructed using fourth-generation sawbones (#3404, composite bone). A total of 24 sawbones with a distal third humeral shaft fracture was randomly divided into three Groups: A,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…This approach may also increase the stability of fixation, especially in cases of severe osteoporosis, periprosthetic fractures, and pathological fractures requiring biplanar fixation. Biomechanical studies of the human skeleton have shown that anteromedial plates provide better stability than anterolateral or posterolateral plates in the treatment of mid-humeral fractures, and that the anteromedial minimally-invasive approach is not suitable for the treatment of proximal humeral fractures due to the lack of adequate fixation sites [ 26 ]. A dual plate can be used in combination with an anterolateral or lateral approach to reconstruct the medial and lateral columns of the distal humerus while preserving blood supply to the surrounding soft tissues and hastening fracture healing [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach may also increase the stability of fixation, especially in cases of severe osteoporosis, periprosthetic fractures, and pathological fractures requiring biplanar fixation. Biomechanical studies of the human skeleton have shown that anteromedial plates provide better stability than anterolateral or posterolateral plates in the treatment of mid-humeral fractures, and that the anteromedial minimally-invasive approach is not suitable for the treatment of proximal humeral fractures due to the lack of adequate fixation sites [ 26 ]. A dual plate can be used in combination with an anterolateral or lateral approach to reconstruct the medial and lateral columns of the distal humerus while preserving blood supply to the surrounding soft tissues and hastening fracture healing [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…No significant biomechanical difference between fixations with 2 or 3 locking screws per fracture segment were found [34]. A biomechanical study by Zheng et al assessed the various plate positions using artificial bone (antero-medial, antero-lateral und posterior) but detected no relevant differences [35].…”
Section: Humeral Shaftmentioning
confidence: 97%
“…Plates and screws are treated as the ideal fixation device despite the recent advances in the implants. 12 Humerus has been approached through different approaches, and each of them has its advantages and disadvantages. 13 Concerning the shape and structure of humerus, the anterior and anteriormedial surface of humerus is flat, allowing accurate seating of plate compared to the lateral surface, which contains the attachment of deltoid muscle limits proper seating of plate over it.…”
Section: Discussionmentioning
confidence: 99%